Police involvement in residential child care - Neil Gentleman (Scottish Journal of Residential Child Care)
The criminalisation of young people in residential care is a matter of concern for everyone. Young people who are looked after away from home are three times more likely to be charged with offences than those in the general population (NACRO, 2003; Taylor, 2006). In the last five years, figures in relation to youth offending indicate an increased likelihood of reaching Persistent Young Offender (PYO) status if you are accommodated in a residential unit (Evans, 2007). The definition of PYO is five offending episodes in a six-month period. Figures in Scotland appear to suggest an association between residential child care and the criminalisation of young people.